Displacement monitoring method based on laser projection to eliminate the effect of rotation angle. Issue 15 (November 2019) - Liu, Peng; Liu, Chengcheng; Zhang, Lixiao; Zhao, Xuefeng
Currently, laser technology has become increasingly mature. Semiconductor lasers have the characteristics of small size, long indication distance, long life, and low cost. Therefore, many studies regard them as the launching devices of monitoring system and fix them at the monitoring points of structures to reflect the displacements of the monitoring points through the spots produced by them. However, this method also exhibits a drawback, that is, this method can only be applied to the case where only displacement is generated at the monitoring point and no rotation angle is generated. If the rotation occurs at the monitoring point, the spot displacement is caused by the coupling effect of the displacement and rotation angle at the monitoring point, which will affect the monitoring results significantly. In this article, a method is proposed to decouple the effect of the displacement and angle and eliminate the influence of the angle sufficiently, by projecting the laser spots onto two screens. This method can significantly improve the application scope of the monitoring system and provide the possibility for its application in practical engineering.